2003
DOI: 10.1161/01.cir.0000051455.44919.73
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic or “Silent” Atrial Fibrillation

Abstract: for the Azimilide Supraventricular Arrhythmia Program (ASAP) Investigators Background-Asymptomatic, or "silent" atrial fibrillation could increase the risk of stroke. Little is known about the frequency of asymptomatic atrial fibrillation in patients who also have symptomatic atrial fibrillation; similarly, little is known about the effect of antiarrhythmic drug therapy on asymptomatic atrial fibrillation. Methods and Results-Patients in sinus rhythm with a history of symptomatic atrial fibrillation or atrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Ambulatory ECG recordings and devicebased monitoring have revealed that an individual may experience periods of both symptomatic and asymptomatic AF. [287][288][289][290] Patients in whom the arrhythmia has become permanent often notice that palpitation decreases with time and may become asymptomatic. This is particularly common among the elderly.…”
Section: Fuster Et Al Acc/aha/esc Practice Guidelines E275mentioning
confidence: 99%
“…Ambulatory ECG recordings and devicebased monitoring have revealed that an individual may experience periods of both symptomatic and asymptomatic AF. [287][288][289][290] Patients in whom the arrhythmia has become permanent often notice that palpitation decreases with time and may become asymptomatic. This is particularly common among the elderly.…”
Section: Fuster Et Al Acc/aha/esc Practice Guidelines E275mentioning
confidence: 99%
“…[13][14][15][16][17][18] In the short-term, PAF could be suppressed by antiarrhythmic drugs, but might not be prevented completely 12 and this incompleteness of the conventional antiarrhythmic therapy might promote remodeling and make the AF more refractory. These possibilities are supported, in part, by the existence of asymptomatic PAF, 19,20 which is more common than expected, 19 although it partially alleviated by the use of antiarrhythmic drugs. 12,19 Previous investigators have shown ischemic heart disease and valvular disease as independent risk factors for AF, [21][22][23] and aging and increased left atrial size have been also identified as important risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…These possibilities are supported, in part, by the existence of asymptomatic PAF, 19,20 which is more common than expected, 19 although it partially alleviated by the use of antiarrhythmic drugs. 12,19 Previous investigators have shown ischemic heart disease and valvular disease as independent risk factors for AF, [21][22][23] and aging and increased left atrial size have been also identified as important risk factors. 21 In accordance with those previous reports, our study, using multivariate analysis, revealed that these 4 factors were significant predictors of early chronic AF development.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis is important in preventing morbidity and mortality, which are largely due to stroke. 4,5 Several tools for assessment of AF have been developed, such as transtelephonic monitoring, 24-hour Holter and implantable loop monitoring of electrocardiographic changes. 6 All these techniques have been evaluated in order to better define the presence of paroxysmal arrhythmias such as paroxysmal atrial fibrillation (PAF).…”
Section: 3mentioning
confidence: 99%